2021
DOI: 10.1016/j.resuscitation.2020.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of intravenous alone versus intravenous or intraosseous access for treatment of out-of-hospital cardiac arrest

Abstract: Objective: Obtaining vascular access during out-of-hospital cardiac arrest (OHCA) is challenging. The aim of this study was to determine if using intraosseous (IO) access when intravenous (IV) access fails improves outcomes. Methods: This was a prospective, parallel-group, cluster-randomised study that compared 'IV only' against 'IV + IO' in OHCA patients, where if 2 IV attempts failed or took more than 90 s, paramedics had 2 further attempts of IO. Primary outcome was any return of spontaneous circulation (RO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…203,204 An RCT comparing intravenous only with intravenous plus intraosseous administration of adrenaline in OHCA found a higher yield of vascular access with the addition of intraosseous access but no improvement in return of spontaneous circulation, survival, or neurological outcome. 205…”
Section: Sudden Cardiac Arrest Ventricular Arrhythmias and Inherited ...mentioning
confidence: 99%
“…203,204 An RCT comparing intravenous only with intravenous plus intraosseous administration of adrenaline in OHCA found a higher yield of vascular access with the addition of intraosseous access but no improvement in return of spontaneous circulation, survival, or neurological outcome. 205…”
Section: Sudden Cardiac Arrest Ventricular Arrhythmias and Inherited ...mentioning
confidence: 99%
“…A common theme of the prehospital literature from 2020 was the focus on timeliness in cardiac arrest management. Times to specific endpoints were the primary outcomes of interest in 9 articles 11–20 . Endpoints included time elapsed until recognition of cardiac arrest, contact with first responders, defibrillation, establishment of vascular access, epinephrine administration, resumption of chest compressions after pulse check, and definitive care in a hospital 11–20 .…”
Section: Resultsmentioning
confidence: 99%
“…Times to specific endpoints were the primary outcomes of interest in 9 articles 11–20 . Endpoints included time elapsed until recognition of cardiac arrest, contact with first responders, defibrillation, establishment of vascular access, epinephrine administration, resumption of chest compressions after pulse check, and definitive care in a hospital 11–20 . Overall, although a reduced time to each intervention during resuscitation was not uniformly shown to improve survival or neurologic outcome, no harms from more rapid intervention for each of the parameters listed above were noted.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, a US study reported a 49% success rate on the first attempt [ 20 ], whereas a UK study reported an 81.6% success rate [ 21 ]. This variability is attributed to multiple factors, such as patient-related issues (e.g., collapsed veins, obesity, and fragile skin) and environmental challenges (e.g., limited space, moving ambulances, poor lighting, and difficult patient positioning) [ 22 , 23 ]. In Ulsan, EMS personnel appear to consider patient age and RTI when deciding on IV attempts, contributing to a relatively higher IV success rate.…”
Section: Discussionmentioning
confidence: 99%